Self-regulation of primary education pre-service teachers - Sukowati Sukowati; Ali Mustadi; Ahmad Agung Yuwono Putro; Gunarti Ika Pradewi (Journal of Education and Learning (EduLearn), 2020)
Motivation for the achievements is urgently needed when attending a class. For renforcing the motivation can be obtained through self-regulation this research aimed to discover students’ self-regulation in a private university at Yogyakarta. This research used quantitative approach in the form of survey. The population in this research was all students in Primary school Teacher Education comprising 233 students. Whereas, there were 155 students as  the sample taken by using random sampling technique. Furthermore, students’ self-regulation was measured by using self regulation learning. The data analysis was conducted qualitatively in the form of descriptive or inferential showed by self-regulation in high category comprising 11 students or 7,09%, medium category comprising 97 students or 62,58%, and low category comprising 47 students or 30,32%. The result of this study showed that: (1) self-regulation of prospective primary school teachers was included into medium category, (2) self-regulation had an important role to improve students’ motivation.